Impact of Inclusive Diversity Practices on Psychological Well-Being of Marginalized Community: A Comparative Study of Transgender - Uzma Karamat Baig; Swaleha J. Khowaja; Dr. Humara Adnan; Tabassum Shahzad (Indus Journal of Social Sciences, 2025)
The term "transgender" (TG) refers to a group of people in society who do not identify with the gender that was assigned to them at birth but instead express themselves in ways that are gender-based. Diversity management practices are important for actual and imagined workplace culture changes which can be brought on by different workforce demographics. Due to economic developments nature and circumstances of the workplace, cultural diversity is experienced for gender-based differences and employment legislation. For Transgender (TG) individuals cultural diversity problems are widespread and frequent they encounter prejudice, antagonism, and pressure to manage their identities in social contexts, including the workplace. Negative social events can trigger a wide range of psychological reactions that may have disastrous effects on a TG person's emotional health, quality of work life, and propensity to persist with a company. The present study aims to identify the impact of diversity management practices of TG at the workplace on their psychological well-being. Moreover, psychological well-being affected by negative social practices and behaviors of social groups for the marginalized community was measured through the following research study in both national and international contexts. The correlational research design was used to find the association between the variables and to predict the role of diversity management practices for the psychological well-being of TG, comparing national and international contexts. (N=250) Working TG from Lahore with age ranges (25-65) were selected using a purposive sampling technique. Descriptive statistics of participant characteristics were measured through descriptive analysis, while Pearson product-moment correlation analysis was used to find the association between the variables. Predicting the role of diversity management practices for psychological well-being was measured through multiple regression analysis. Results showed a significant negative association between diversity management practices and the psychological well-being of TG individuals, showing more diverse workplace neglects resulting in less psychological well-being.